Java with BlueJ - McFadyen, Ron; Open Textbook Library (Open Textbook Library, 2016)
This book is Part I of a two-part set that introduces the Java programming language. The text assumes the student will be using the BlueJ development environment and provides some introductory BlueJ material. Our experience has been that BlueJ is easy to learn and provides a good programming environment for the beginner programmer.
1 Introduction -- 2 Basics -- 3 Control Structures -- 4 Classes in the Java Class Libraries -- 5 ArrayLists -- 6 One-Dimensional Arrays -- 7 Designing Java Classes -- 8 A Brief Introduction to Graphical User Interfaces
In English.
Description based on online resource
Keywords: Computer Science -- Textbooks; Programming Languages -- Textbooks